The Sources of Innovation (1988)
This seminal book has become essential reading for students taking courses in technology management and innovation, and for managers who are responsible for strategic planning. The author shows how the initiative to innovate can come not only form a manufacturer, but also from suppliers, and customers. The author calls these lead users , and the term has come into the business lexicon. A video course based on the book was produced by the MIT TV department and has been distributed to many business schools. The Sources of Innovation has become essential to an understanding of how and where technological innovation takes place. For the first time, the book shows how the assumption that technological innovation is generated by manufacturers is inaccurate. Innovation takes place where it creates the most value, and that can be in a variety of locations, from suppliers to end users. Understanding this fact can facilitate the innovation process, leading to faster and better processes and products.